Shariah And Social Reconstructions In Northern Nigeria: Evidence From Niger State Zakat And Endowmwnt Board (2001-2017) - Abdulwahab Danladi Shittu; Shehu Folohun Ismail; Muhammad Nasiru Ndaman (USIM Press, 2024)
VOL. 10 NO. 2 (2022) Page (16-25)